2005
DOI: 10.1021/jf0518913
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant, Antimicrobial, and Antifungal Activities of the Essential Oil of Achillea ligustica All.

Abstract: The chemical composition of the essential oil from flowering tops of Achillea ligustica All. was studied. Samples were collected in different localities of Sardinia (Italy) and hydrodistilled both with Clevenger-type and with simultaneous distillation-extraction apparatus. The yields ranged between 0.88 +/- 0.06 and 0.43 +/- 0.02% (vol/dry wt). The essential oils were analyzed by GC-MS, and a total of 96 components were detected. From a qualitative point of view, irrelevant differences between samples were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 12 publications
2
26
2
3
Order By: Relevance
“…The effectiveness of the two essential oils was comparable, with growth inhibition zones of 10 − 13 mm; C. albicans only was particularly susceptible, with an inhibition zone of 24 mm ( Table 2). These results agree with those previously reported by Tuberoso et al [4] with essential oils from Sardinia (Italy) at a dose of 20 μl but, possibly because of their different composition, the essential oils from Sicily seem to be equally effective at a dose of only 10 μg. Furthermore, they showed good antibacterial activity against Hafnia alvei, Listeria monocytogenes and Bacillus cereus ( Table 2 Antimicrobial activity of the essential oil from leaves and flowers of Achillea ligustica (10 μg/plate); mean of three replication±SD.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The effectiveness of the two essential oils was comparable, with growth inhibition zones of 10 − 13 mm; C. albicans only was particularly susceptible, with an inhibition zone of 24 mm ( Table 2). These results agree with those previously reported by Tuberoso et al [4] with essential oils from Sardinia (Italy) at a dose of 20 μl but, possibly because of their different composition, the essential oils from Sicily seem to be equally effective at a dose of only 10 μg. Furthermore, they showed good antibacterial activity against Hafnia alvei, Listeria monocytogenes and Bacillus cereus ( Table 2 Antimicrobial activity of the essential oil from leaves and flowers of Achillea ligustica (10 μg/plate); mean of three replication±SD.…”
Section: Resultssupporting
confidence: 93%
“…Very recently, [4] a study was published on the essential oil composition from flowering aerial parts of this species collected in eight different localities of Sardinia where the chemical composition was very different from that reported here. Another recent study of the aerial part of this species collected in Corsica also reported a different composition of the essential oil that contained camphor (21.3%), santolina alcohol (19.3%), artemisia ketone (5.9%), borneol (6.2%) and bornyl acetate (3.5%) as the main constituents [5].…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…D 1 , D 2 , D 3 depressurization step (10 min). C continuous extraction step (120 min) (Zaidul et al 2007) (Pereira et al 2004) as antiviral, antibacterial, anti-inflammatory, antioxidant, anti-spasmodic, and others (Chao et al 2005;Gornemann et al 2008;Kim et al 1995;Jirovetz et al 2006;MimicaDukic et al 2004;Sivropoulou et al 1997;Tuberoso et al 2005). Due to these properties, essential oils have been used as ingredients of cosmetics, food, and pharmaceutical products.…”
Section: Essential Oilsmentioning
confidence: 99%
“…This can be due to the use of fresh material instead of dry one. In literature, the following values were reported: 0.4 and 0.13 -0.90% for population from Corsica [17] [18], respectively, 0.43 -0.88% for population from Sardinia [19], and 0.38 -0.48% for population from Sicily [20].…”
mentioning
confidence: 99%